2020
DOI: 10.1093/ehjcr/ytaa354
|View full text |Cite
|
Sign up to set email alerts
|

A concealed carcinoid cardiac metastasis uncovered by comprehensive cardiovascular magnetic resonance-based tissue characterization: a case report

Abstract: Background Cardiac metastases of carcinoid tumours are extremely rare, and their diagnosis poses a significant challenge. A variety of techniques has been reported in the literature for this purpose, ranging from echocardiogram to the Indium-111 Octreotide, positron emission tomography using specific tracers, and biopsy. Occasionally, the diagnosis is only made post-mortem. Recently, CMR (cardiovascular magnetic resonance) has been added to the diagnostic toolkit. This case report describes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A variety of techniques have been reported for this purpose, ranging from echocardiogram to the Indium‐111 octreotide, PET using specific tracers, cardiovascular magnetic resonance, and biopsy. Occasionally, the diagnosis is made post‐mortem 4 . Although the majority of larger masses are detected by echocardiography, lesions smaller than 1 cm may be missed, 12 while PET/CT might contribute to earlier and more frequent detection 3 …”
Section: Discussionmentioning
confidence: 99%
“…A variety of techniques have been reported for this purpose, ranging from echocardiogram to the Indium‐111 octreotide, PET using specific tracers, cardiovascular magnetic resonance, and biopsy. Occasionally, the diagnosis is made post‐mortem 4 . Although the majority of larger masses are detected by echocardiography, lesions smaller than 1 cm may be missed, 12 while PET/CT might contribute to earlier and more frequent detection 3 …”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic information from a PET/CT scan is superior to that of PET or CT alone. 53 A nuclear medicine modality, PET, is fused with a high-resolution anatomical imaging modality. PET/CT offers the advantage of accurately localizing increased metabolic activity to specific anatomic locations, which may be difficult with PET alone.…”
Section: Pet/ctmentioning
confidence: 99%
“…There are several PET radioisotopes (Tables 1, 3) that can also be used for imaging of PHEOs and PGLs. 53,54 Table 3 contains not only the important studies and clinical cases where PET/ CT proved its diagnostic value in this field, but also previous meta-analyzes where it is clear that in patients with suspected PGLs, 18 F-DOPA PET or PET/CT demonstrated high sensitivity and specificity. 36 Calissendorf et al 17 investigated patients with ileal NETs and found a frequency of 4.3% of cardiac metastasis One patient had cardiac surgery while three were treated with somatostatin analogs.…”
Section: Pet/ctmentioning
confidence: 99%